2003
DOI: 10.1021/bi026868e
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Function Analysis of a Series of Novel GIP Analogues Containing Different Helical Length Linkers

Abstract: Glucose-dependent insulinotropic polypeptide (GIP1-42) is a potent glucose-lowering intestinal peptide hormone. The equipotent GIP1-30NH2 was structurally modified by linking N- and C-terminal fragments with several different linkers. Substitution of the middle region of GIP by a flexible aminohexanoic linker resulted in greatly reduced binding affinity and reduction or complete loss of bioactivity. Connection of the bioactive domains GIP1-14 and GIP19-30NH2 by EKEK or AAAA linkers resulted in peptide agonists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 44 publications
4
13
1
Order By: Relevance
“…We have also found that GIP is 20% helical in 20 mM phosphate buffer, pH 7.0, increasing up to 26% when in 20 mM acetate buffer, pH 4.0. These results are in contrast with studies of Manhart et al (38), in which they reported a helical content of 11% for GIP in 20 mM phosphate buffer, pH 7. Studies in the near-UV (results not shown), carried out for 0.95 mM GIP samples in phosphate buffer (20 mM, pH 7.0) and unbuffered (pH 3.0, uncorrected), show spectra similar to those found for folded proteins (37).…”
Section: Discussioncontrasting
confidence: 99%
“…We have also found that GIP is 20% helical in 20 mM phosphate buffer, pH 7.0, increasing up to 26% when in 20 mM acetate buffer, pH 4.0. These results are in contrast with studies of Manhart et al (38), in which they reported a helical content of 11% for GIP in 20 mM phosphate buffer, pH 7. Studies in the near-UV (results not shown), carried out for 0.95 mM GIP samples in phosphate buffer (20 mM, pH 7.0) and unbuffered (pH 3.0, uncorrected), show spectra similar to those found for folded proteins (37).…”
Section: Discussioncontrasting
confidence: 99%
“…4, Table 2). In agreement with previous work using other cell jpet.aspetjournals.org lines (Manhart et al, 2003), equilibrium binding of the radioligand to HEK293 cells expressing the recombinant GIP-R was reached within a 7-h incubation period at 4°C (data not shown). Consistent with the marked reduction in agonist potency at the C46S isoform (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Several studies have shown that N-terminal GIP residues confer significant affinity toward the full-length receptor and are essential for activation of the GIPR (37)(38)(39)(40). It has also been reported that the biological activity can be influenced by modifying the degree of ␣-helicity of the ligand (41). In the present study, thermodynamic and spectroscopic analysis of the GIPR ECD-GIP 1-42 complex formation provide evidence for structural reorganization during binding (SI Text).…”
Section: Discussionsupporting
confidence: 54%